A intentio dos atos humanos no Scito Te Ipsum de Pedro Abelardo - Silva, Pedro Rodolfo Fernandes da (2008)
This work presents a reading of the Scito Te Ipsum of Peter Abelard (1079- 1142), focusing the core of morality: the intentio. In Abelard s conception, moral acts are in themselves indifferent. Morality abide exclusively in agent s consent and in the intention that precedes action. When the agent consents, consciously, in the contempt of God, commits sin, although he doesn t execute the action. Sin is not, therefore, in vice, neither in bad will. These, would be better called, a disease of the soul that push man and against which he has to fight to deserve glory s crown